1991
DOI: 10.1128/iai.59.6.1932-1940.1991
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic activity in the periodontopathogen Porphyromonas gingivalis: kinetics of enzyme release and localization

Abstract: Porphyromonas gingivalis W50, W83, A7A1-28, and ATCC 33277 were investigated for their abilities to lyse sheep, human, and rabbit erythrocytes. All of the P. gingivalis strains studied produced an active hemolytic activity during growth, with maximum activity occurring in late-exponential-early-stationary growth phase. The enzyme was cell bound and associated with the outer membrane. Fractionation of P. gingivalis W50 localized the putative hemolysin almost exclusively in the outer membrane fraction, with sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 52 publications
2
69
0
Order By: Relevance
“…These observations point to the fact that hemolytic activity and RGP activity are distinct from each other. The expression of P. gingivalis hemolytic activity has shown to be regulated by iron [3]. Excess iron has shown to depress hemolytic activity [3,6], while addition of the iron-chelator BPD increases hemolytic activity [3,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations point to the fact that hemolytic activity and RGP activity are distinct from each other. The expression of P. gingivalis hemolytic activity has shown to be regulated by iron [3]. Excess iron has shown to depress hemolytic activity [3,6], while addition of the iron-chelator BPD increases hemolytic activity [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of P. gingivalis hemolytic activity has shown to be regulated by iron [3]. Excess iron has shown to depress hemolytic activity [3,6], while addition of the iron-chelator BPD increases hemolytic activity [3,6]. Genco et al [13] have reported a higher hemolytic activity in a hemin uptake de¢cient mutant of P. gingivalis as compared to the wild-type strain.…”
Section: Discussionmentioning
confidence: 99%
“…The gingival pocket is normally at neutral pH, however P. intermedia grown on agar is in an acidic environment generated by main end products such as acetic acid and succinic acid. Iron limitation resulted in signi¢cantly higher hemolysin production of P. gingivalis [9]. A similar e¡ect of iron is known for diphtheria toxin, Pseudomonas aeruginosa exotoxin A, and other toxins [24].…”
Section: Discussionmentioning
confidence: 70%
“…Hoshi et al [13] reported that the mode of action of the hemolysin from P. gingivalis was 'hotcold' lysis, similar to hemolysin from Leptospira canicola [11], Staphylococcus aureus [23] or Clostridium welchii [12]. However, hemolytic activity by prevolysin O did not increase with chilled treatment after incubation at 37 ‡C for 1 h. Some hemolytic substances from Gram-negative bacteria are activated by divalent cations [9]. The present hemolysin from P. intermedia did not possess such a property.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation